Molecular identification of parakeet species by mitochondrial cytochrome B marker - VINOTH KUMAR. S; BARATHI. S (International Journal of Pharma and Bio Sciences, 2016)
Birds in pet trade are still a continuing issue beyond protection and conservation. Parakeets and allies are the majority among reported species. Identifying a species under forensic investigation is a challenge, as many cases involve trade of newly hatched chicks, juveniles and eggs where morphometric identification fails. Molecular identification using selective DNA markers, especially mitogenomic markers like cytochrome b, were found persuasive in resolving these issues. In this study, three parakeet species were analyzed for species identification using cytochrome b marker. Naturally shed feather samples were used for DNA extraction and PCR amplification and sequencing of cyt b region were done. Sequence analyses and phylogenetic analyses were carried out using various methods and bioinformatics tools. The results from each analysis were pooled and the species were identified as Psittacula eupatria, P. krameri and P. roseata. This approach using multiple methods could be expedient for the scientific prosecution of wildlife crime cases.